User perception and satisfaction towards facilities of private highways in Malaysia / Muhammad Fikri Jamari - Jamari, Muhammad Fikri (Faculty of Architecture, Planning and Surveying, 2013)
This thesis is about a study of user perception and satisfaction towards facilities of highways in Malaysia. In this study, there are three highways concessionaire companies chosen as a case study which LATAR Expressway, Guthrie Corridor Expressway and LEKAS Expressway. User of highways will be the key to succeed this study where the questionnaires will be distributed to them and most of information will be asked for them and there are interview of officer in-charge at highway concessionaires companies. Issues that always arise involving highway-care related facilities are provided by the highway concessionaire. Then, there are issues of upgrading the facilities of North South Highway along the highway with cost of RM41 million and issues of safety where which highway users complained about the facilities that not functioned well and others issue which brings to the making of this study. This study was conducted to identify the facilities provided by the highway concessionaires which are not all the same highway facilities. For example, LEKAS Expressway and Guthrie Corridor Expressway have laybys while LATAR Expressway not has laybys and other facilities. Then, there are results of user perception and satisfaction where this results shows the best highways and their reputations on how they handle their facilities and properties to ensure the satisfaction of user of their highways and by referring these results of users perception and satisfaction, there are recommendation provided to ensure the highways can kept their reputation and performance to the maximum. Lastly, how the highway concession company manages their properties. They need to fulfill all the requirements outlines by authorities which are Lembaga Lebuhraya Malaysia (LLM) and need to maintain and upgrade the facilities based on the Standard Operating Procedure (SOP) to ensure that users that use their facilities will satisfy and not bear any problems. Thus, this study was conducted.